Patients with Lemierre syndrome have a high risk of new thromboembolic complications, clinical sequelae and death: an analysis of 712 cases. (18th June 2020) - Valerio, L.; Zane, F.; Sacco, C.; Granziera, S.; Nicoletti, T.; Russo, M.; Corsi, G.; Holm, K.; Hotz, M.‐A.; Righini, C.; Karkos, P. D.; Mahmoudpour, S. H.; et al.
Abstract: Background: Lemierre syndrome is characterized by head/neck vein thrombosis and septic embolism usually complicating an acute oropharyngeal bacterial infection in adolescents and young adults. We described the course of Lemierre syndrome in the contemporary era. Methods: In our individual‐level analysis of 712 patients (2000–2017), we included cases described as Lemierre syndrome if these criteria were met: (i) primary site of bacterial infection in the head/neck; (ii) objectively confirmed local thrombotic complications or septic embolism. The study outcomes were new or recurrent venous thromboembolism or peripheral septic lesions, major bleeding, all‐cause death and clinical sequelae. Results: The median age was 21 (Q1–Q3: 17–33) years, and 295 (41%) were female. At diagnosis, acute thrombosis of head/neck veins was detected in 597 (84%) patients, septic embolism in 582 (82%) and both in 468 (80%). After diagnosis and during in‐hospital follow‐up, new venous thromboembolism occurred in 34 (5.2%, 95% CI 3.8–7.2%) patients, new peripheral septic lesions became evident in 76 (11.7%; 9.4–14.3%). The rate of either was lower in patients who received anticoagulation (OR: 0.59; 0.36–0.94), higher in those with initial intracranial involvement (OR: 2.35; 1.45–3.80). Major bleeding occurred in 19 patients (2.9%; 1.9–4.5%), and 26 died (4.0%; 2.7–5.8%). Clinical sequelae were reported in 65 (10.4%, 8.2–13.0%) individuals, often consisting of cranial nerve palsy ( n  = 24) and orthopaedic limitations ( n  = 19). Conclusions: Patients with Lemierre syndrome were characterized by a substantial risk of new thromboembolic complications and death. This risk was higher in the presence of initial intracranial involvement. One‐tenth of survivors suffered major clinical sequelae. Abstract :